(untitled) (World Bulletin of Public Health, 2024)
Diabetes mellitus (DM) and cardiovascular diseases (CVD), along with cancer and chronic respiratory diseases, are the most formidable “killers” in the world and cause approximately 35 million deaths per year [World Health Organization, 2018]. Metabolic syndrome (MS) is the basis for the development of non-insulin-dependent diabetes (NIDDM), as well as CVD [Simmons R. et al., 2010; Alexandrov O.V. et al., 2016; Holvoet P, 2018; Van Zwieten P.A., Mancia G., 2015].